G457(P) Cases of neonatal spontaneous intestinal perforation in a tertiary care centre over a 5 year period. (24th May 2017) - Stewart, EJ; Granger, C; O'Shea, J
Abstract : Background: Spontaneous intestinal perforation (SIP) is a serious complication of prematurity. Associations include extreme prematurity, early postnatal steroids and early use of indomethacin. Non-invasive respiratory support in preterm infants is increasingly being used both as primary and post-extubation support. Two years ago we changed the method used to deliver non-invasive respiratory support and now use higher flows and pressures. Aim: To review all cases of neonatal spontaneous intestinal perforation in the last five years and ascertain those infants with associated risk factors. We also sought to determine if the frequency of the condition has increased since the introduction of higher pressure, higher flow non-invasive respiratory support. Methods: This was a retrospective cohort study of the Badger electronic database for a tertiary neonatal and surgical centre. Results: 22 infants were diagnosed with SIP in the West of Scotland between June 2012 and December 2016. 5 infants (23%) had incomplete data. There were 4, 1, 5, 2 and 5 cases per year in each of these years respectively. Their mean gestation and birth weights were 28+1 and 1234g. Median day of diagnosis was 5 (0–62) days of age. 15 infants (68%) had received antenatal steroids. 4 infants (18%) had received medical treatment for patent ductus arteriosus. 2 infants (9%) received post natal dexamethasone. 7 infants had hydrocortisone or inotropes. 11 infants were partially or fully enterally fed. At diagnosis, 6 infants were on non-invasive respiratory support and 8 infants were ventilated. 4 infants had been recently intubated. 2 infants were on no respiratory support. 6 (27%) infants were treated conservatively and 16 (73%) surgically. 5 infants died. Conclusion: Despite changes in respiratory management with higher pressure non-invasive support, rates of spontaneous intestinal perforation have not increased. Most infants had at least one associated risk factor.